Helicobacter pylori Prevalence in Laparoscopic Sleeve Gastrectomy Specimen - Nada A. Sabbah; Carla Z. Saoud; Mary Deeb; Selim M. Nasser (Gastroenterology Research and Practice)
Introduction. Laparoscopic sleeve gastrectomy (LSG) has become a common surgical procedure. The value of routine histopathologic examination of the LSG specimens remains, however, a controversial issue. Helicobacter pylori was the most prevalent finding in several previous studies, but the overall results were dissimilar. We aim to assess the prevalence of Helicobacter pylori and other histopathologic findings in LSG specimens and the effect of increasing the number of sections for histology, from LSG specimens, on the rates of abnormal findings. Methods. We retrospectively reviewed the histopathologic data of all patients who had undergone LSG, in a tertiary care center, over a 4-year period (n=481). Patient characteristics and histopathologic findings were recorded and analyzed. Results. Inactive chronic gastritis was the most common histopathologic finding (62.16%) followed by Helicobacter pylori gastritis (35.34%). Intestinal metaplasia was identified in 1.66% of the cases. There was no diagnosis of malignancy. Increasing the number of sections submitted for histopathologic examination resulted in a significantly higher rate of H. pylori gastritis detection. Conclusion. Routine histopathologic examination of LSG specimens may detect H. pylori in a significant proportion of patients, and increasing the number of sections for histology from LSG specimens improves the rate of detection of this bacterium and identifies individuals who may benefit from treatment.